Fundamentalist research and its relationship to the promotion of social peace Kurdish society is a model - أميد نجم الدين جميل المفتي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Some themes of the basics of Islamic Al-Fiqh with its relations and setting up the social peace - Kurdish Society is an example-. The social peace temes are those width items which contains many more parts of life which relates with the society and individuals for all scientific fields, because of hapiness and invention thoughts of life relates to this source, all of these subjects proof the importance of this matters. As a suitable subject due to the following scientifical subjects of (Principles of AlFiqh), We are trying to focus on this, which has a relation with social peace, all are collected on the roof of achieving interests and neglecting of all badnesses, all of legitimate texts are focusing on it clearly or unclearly. The matter demands to divide into four main and finally themes which are: 1- First, We are trying to speak concentrating with the Islamic scientific relations with social peaces, which are collected by scientific believes, legitimate practical sciences and spiritual sciences. 2- Then it was focused on social peace relations, objects and proofs and legitimate rules for the scientifical basic of Al-Fiqh. 3- Next, It was tried refering to social peace placement due to the scientists talks -Fatawa. 4- Finally, making differenciate between us and the others through our believes is the matter, how it could be treating through the scientifical basics of islamic Al-Fiqh and social peaces through clearing rules. For all these matters, Kurdish society is our example for this research. Finally we were trying to show all basic points for readers. We will hope to serve the research fields, social and religious fields for native readers and students by this research.